Cambodia - More Efficient Government Spending for Strong and Inclusive Growth : Integrated Fiduciary Assessment and Public Expenditure Review - World Bank (World Bank, 2012)
Cambodia has made substantial progress in economic reconstruction since the 1993 elections helped return peace to the war ravaged country. The report is organized as: the remainder of chapter one presents the strategic background, including macroeconomic and fiscal developments. The chapter concludes with options for restoring and expanding the government's fiscal space. Chapter two discusses the level and composition of public spending. Chapters three, four and five discuss the level, composition and effectiveness of government spending on agriculture, health, and education, respectively. The analysis suggests that government spending in these areas is lower relative to Gross Domestic Product (GDP) than in countries with similar levels of income per capita. Chapter six discusses Cambodia's progress and challenges in reforming public expenditure policy and public finances. The chapter underscores the key areas where additional attention is needed to help advance the reform agenda.